Protestant Ireland and the English Parliament, 1641-1647 - Armstrong, Robert (Trinity College (Dublin, Ireland). Department of History, 1996)
This thesis considers the relations between the Protestants of Ireland and the Long Parliament from the outbreak of the 1641 Rising until mid -1647. It aims to show that Ireland was a central concern of Parliament's throughout these years, as being an element in the self-definition of the parliamentary 'cause' of one of religious and national defence; and that the eventual accommodation of Irish Protestants and Parliament was founded on a compatibility of objectives, based on victory in the Irish war, strong enough to overcome constitutional scruples if not pressed too hard. The principal sources used are the records of Parliament and of its Irish committees, and collections relating to Irish Protestant figures, most notably the Carte collection of Ormond papers. Newsletters have been sampled where it seemed most appropriate and contemporary pamphlets and other works have been consulted.
Keywords: History, Ph.D.; Ph.D. Trinity College Dublin